(untitled) (Journal of actual problems of jurisprudence, 2019)
This paper deals with the introduction of distance learning technologies in the educational process for the teaching of legal disciplines. Describe the technologies and methods of implementation of distance education, as well as the prospects of development of this technology in the department. Keywords: distance learning, distance learning technology, educational process, innovative teaching methods, information systems, information technology.